2022
DOI: 10.1073/pnas.2204050119
|View full text |Cite
|
Sign up to set email alerts
|

A de novo protein catalyzes the synthesis of semiconductor quantum dots

Abstract: De novo proteins constructed from novel amino acid sequences are distinct from proteins that evolved in nature. Construct K (ConK) is a binary-patterned de novo designed protein that rescues Escherichia coli from otherwise toxic concentrations of copper. ConK was recently found to bind the cofactor PLP (pyridoxal phosphate, the active form of vitamin B 6 ). Here, we show that ConK catalyzes the desulfurization of cysteine to H 2 S, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Another random protein was found to promote survival in high concentrations of copper 67 , but the underlying molecular mechanism remains unknown. This random protein was also studied in vitro and found to catalyze the conversion of cysteine to H 2 S in a pyridoxal phosphate dependent manner 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another random protein was found to promote survival in high concentrations of copper 67 , but the underlying molecular mechanism remains unknown. This random protein was also studied in vitro and found to catalyze the conversion of cysteine to H 2 S in a pyridoxal phosphate dependent manner 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A complementary approach to investigating de novo gene birth involves the characterization of randomly generated proteins and studying whether they can benefit cells. Prior work has examined in silico and in vitro properties of such random sequences, including their predicted ability to fold into secondary structures 16 , solubility 17 , ATPase activity 18 , or potential affinity for different molecules [19][20][21][22] . However, cellular functions for random genes have rarely been demonstrated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Spangler et al identified a de novo protein that was capable of producing CdS quantum dots with size tunable properties. 114 De novo proteins stand in stark contrast to natural proteins as they are not found in nature, and instead are designed following a polar-non polar amino acid motif. Thus, de novo proteins are not expected to have any functionality.…”
Section: ■ General Theory Of Nanoparticle Nucleation and Growthmentioning
confidence: 99%
“…Other manufacturing methods are being developed. For example, Spangler et al (2022) have developed new quantum dot manufacturing processes involving new synthetic proteins that avoid much of the use of toxic materials that also allow manufacturing of the dots to be at room temperature. When a photon is absorbed, a carrier is excited from the valence band to the conduction band in the nano‐crystal.…”
Section: Quanta Image Detectorsmentioning
confidence: 99%